Efficient near-infrared response photocatalytic composite crystal as well as preparation method and application thereof

The ternary composite silver phosphate crystals prepared by the biomimetic mineralization strategy solved the problems of light absorption range and stability of semiconductor photocatalysts, and achieved the effect of efficient degradation of Rhodamine B under near-infrared light.

CN121155682AActive Publication Date: 2025-12-19JINAN UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511432867.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-09
Publication Date
2025-12-19
Estimated Expiration
2045-10-09

AI Technical Summary

Technical Problem

Existing semiconductor photocatalysts suffer from low efficiency in separating photogenerated electron-hole pairs, slow migration rates, severe photocorrosion, chemical instability, and limited light absorption range, which restricts their application in energy conversion and environmental governance.

Method used

A biomimetic mineralization strategy was employed to prepare a ternary composite silver phosphate crystal with high efficiency near-infrared response. By embedding NaYF4:Yb,Tm upconversion nanoparticles with MOF nanocomposites and silver phosphate crystals, a multifunctional MOF nanocomposite was formed, which extended the light absorption range to the near-infrared and improved cycling stability.

Benefits of technology

This study achieved efficient degradation of Rhodamine B under near-infrared light while maintaining excellent cycle stability, breaking through the performance bottleneck of existing semiconductor photocatalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121155682A_ABST
    Figure CN121155682A_ABST
Patent Text Reader

Abstract

The invention provides an efficient near-infrared response photocatalytic composite crystal as well as a preparation method and application thereof, and belongs to the technical field of preparation of non-traditional semiconductor crystals. According to the preparation method, upconversion nanoparticles NaYF4: Yb, Tm and MOF are fused through a one-step method to obtain an upconversion functionalized MOF nanocomposite, and then the multifunctional MOF nanocomposite is prepared through amidation reaction and reversible addition-fragmentation chain transfer polymerization. And finally, fusing the composite nanoparticles with silver phosphate crystals through a biomimetic synthesis strategy to obtain the multifunctional ternary composite silver phosphate crystals. According to the method, the problems of limitation of the wavelength range of silver phosphate absorption light and light corrosion are solved, the photocatalytic composite crystal can effectively degrade rhodamine B when being used under near-infrared light, and excellent cycling stability is achieved while the leading near-infrared light catalytic activity is kept.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of preparation of unconventional semiconductor crystals, and particularly relates to a high-efficiency near-infrared response photocatalytic composite crystal and a preparation method and application thereof. BACKGROUND

[0002] Semiconductors can absorb photons in solar energy equal to or greater than their band gap, generate electron-hole pairs and drive various photo-induced chemical transformations, so that such materials play an important role in the process of converting "solar energy into chemical energy". However, many problems faced by semiconductor photocatalysts, such as low separation efficiency of photo-generated electron-hole pairs, slow migration rate, serious photo-corrosion, chemical instability, and limited light absorption range, have become key challenges limiting their practical application. Breaking through these bottlenecks is crucial for promoting the application of semiconductor photocatalysis in the field of energy conversion and environmental governance.

[0003] In nature, organisms can precisely control the formation and structure of biological minerals through precise interaction between biological macromolecules and mineral crystals. The resulting multi-component hierarchical structure endows biological minerals with excellent mechanical properties and functional adaptability. Inspired by this, scientists actively explore biomimetic mineralization strategies to artificially synthesize high-performance composite crystals. However, due to the difficulty in rationally regulating the interaction between organic matrix and mineral crystals at the molecular level and breaking the interface incompatibility, biomimetic mineralization still faces great challenges. SUMMARY

[0004] Therefore, the present application aims to provide a high-efficiency near-infrared response photocatalytic composite crystal and a preparation method and application thereof.

[0005] In order to achieve the above-mentioned purpose, the present application provides the following technical solutions: One of the technical solutions of the present application is a preparation method of a high-efficiency near-infrared response photocatalytic composite crystal, comprising the following steps: Disperse NaYF4:Yb,Tm up-conversion nanoparticles in solution 1, reaction 1, to obtain up-conversion functionalized MOF nanocomposites; the solute in the solution 1 is zirconium salt, organic ligand and glacial acetic acid; The up-conversion functionalized MOF nanocomposites are subjected to amidation reaction with chain transfer agent CPCP under the action of a coupling agent, to obtain up-conversion functionalized MOF nanocomposites grafted with CPCP; The up-conversion functionalized MOF nanocomposites grafted with CPCP are subjected to polymerization reaction with polymer monomers under the action of an initiator, to obtain multifunctional MOF nanocomposites; The multifunctional MOF nanocomposite is dispersed in a silver ammine solution to obtain a mixed solution; then, sodium dihydrogen phosphate is added to the mixed solution, and the reaction is carried out after standing to obtain the photocatalytic composite crystal.

[0006] The second technical scheme of the present application is the high-efficiency near-infrared responsive photocatalytic composite crystal prepared by the preparation method.

[0007] The third technical scheme of the present application is the application of the high-efficiency near-infrared responsive photocatalytic composite crystal in photocatalytic degradation of rhodamine B.

[0008] The present application discloses the following technical effects: The high-efficiency near-infrared responsive photocatalytic composite crystal prepared by the present application is a ternary composite silver phosphate crystal, and the specific preparation steps are as follows: a polymer chain is modified on the surface of NaYF4:Yb,Tm@MOF to obtain a multifunctional MOF nanocomposite with excellent colloidal stability, and then the nanocomposite is fused with a silver phosphate host crystal as a guest nanoparticle through a biomimetic synthesis-inlay strategy. This method solves the problems of the limitation of the absorption wavelength range of silver phosphate (traditional silver phosphate cannot use near-infrared light) and poor recyclability.

[0009] The present application prepares a ternary composite silver phosphate crystal through a biomimetic inlay strategy, and the ternary composite silver phosphate crystal is used for effectively degrading rhodamine B under near-infrared light. While maintaining the leading near-infrared photocatalytic activity, the ternary composite silver phosphate crystal has excellent cycle stability. The present application provides an effective strategy for rationally designing the next generation of photocatalysts to break through the shackles of existing problems. BRIEF DESCRIPTION OF DRAWINGS

[0010] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings needed in the embodiments will be briefly introduced as follows. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can be obtained by those skilled in the art without creative labor.

[0011] Figure 1 The transmission electron microscope picture of the NaYF4:Yb,Tm upconversion nanoparticle obtained in Example 1; Figure 2 The transmission microscope picture of the upconversion functionalized UiO-66-NH2 nanocomposite obtained in Example 2; Figure 3 The transmission microscope picture of the multifunctional UiO-66-NH2 nanocomposite obtained in Example 3; Figure 4 The scanning electron microscope pictures of the ternary composite silver phosphate crystal obtained in Example 4 under different magnifications, wherein a is 20 μm, and b is 1 μm. Figure 5 FTIR spectra of different materials in Example 1-4; Figure 6 Point-line graph of the degradation degree of Rhodamine B under near-infrared light driving with different catalysts in performance test over time; Figure 7 Constant column graph of the degradation degree of the ternary composite silver phosphate crystal (NaYF4:Yb,Tm@UiO-66-PMAA@Ag3PO4) obtained in Example 4 under near-infrared driving in ten cycles of catalytic cycles in performance test. DETAILED DESCRIPTION

[0012] The various illustrative embodiments of the present application will now be described in detail in connection with the accompanying drawings. This description is made for illustrative purposes only and is not intended to limit the application as set forth in the claims.

[0013] It should be understood that the terms used herein are merely descriptive, but are not intended to limit the application. In addition, for numerical ranges in the present application, it should be understood that each intermediate value between the upper limit and the lower limit of the range is also specifically disclosed. Each smaller range between any stated value or stated range, and any other stated value or intermediate value in the stated range is also encompassed within the present application. The upper and lower limits of these smaller ranges can be independently included or excluded from the range.

[0014] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present application, preferred methods and materials are described. All publications mentioned in this specification are herein incorporated by reference to disclose and describe the methods and / or materials in connection with which the publications are cited. The citation of any reference in this specification is not intended as an admission that the reference is prior art, but rather that the reference is part of the technical literature that is relevant to the content of this specification.

[0015] Many modifications and variations of this application specification can be made without departing from its scope or spirit, which will be apparent to those skilled in the art. Other embodiments resulting from the combination of features of the application specification will be apparent to those skilled in the art. The present application specification and examples are merely illustrative.

[0016] As used herein, "comprise", "comprising", "have", "having", "include", "including", "contain", "containing", and the like, are open-ended terms that are intended to mean including but not limited to.

[0017] In the present application, unless otherwise specified, room temperature means 25±5℃.

[0018] The application firstly obtains up-conversion nanoparticles with uniform particle size distribution and good colloidal stability through a solvothermal synthesis method; then fuses the up-conversion nanoparticles NaYF4:Yb, Tm with MOF (UiO-66-NH2) to obtain up-conversion functionalized MOF (UiO-66-NH2) nanocomposites through a one-step method, and then prepares multifunctional MOF (UiO-66-NH2) nanocomposites through an amidation reaction and a reversible addition-fragmentation chain transfer polymerization; finally fuses the composite nanoparticles with silver phosphate crystals to obtain multifunctional ternary composite silver phosphate crystals through a biomimetic synthesis strategy.

[0019] The application provides a preparation method of a high-efficiency near-infrared response photocatalytic composite crystal. The NaYF4:Yb, Tm up-conversion nanoparticles are dispersed in solution 1, reaction 1 is performed, and up-conversion functionalized MOF nanocomposites are obtained; the solute in the solution 1 is a zirconium salt, an organic ligand and an adjusting agent; The up-conversion functionalized MOF nanocomposites perform an amidation reaction with a chain transfer agent CPCP under the action of a coupling agent, and up-conversion functionalized MOF nanocomposites grafted with CPCP are obtained; The up-conversion functionalized MOF nanocomposites grafted with CPCP perform a polymerization reaction with a polymerization monomer under the action of an initiator, and multifunctional MOF nanocomposites (the particle size of the multifunctional MOF nanocomposites is about 100-400 nm) are obtained; The multifunctional MOF nanocomposites are dispersed in a silver ammine solution to obtain a mixed solution; then sodium dihydrogen phosphate is added to the mixed solution, and the photocatalytic composite crystal is obtained after standing and reaction.

[0020] In the preferred embodiment of the application, the preparation method of the NaYF4:Yb, Tm up-conversion nanoparticles is as follows: rare earth salts, ammonium fluoride, sodium chloride and a capping agent are added to a solvent to perform reaction 2.

[0021] Further preferably, the rare earth salt comprises 77%-98% of Y 3+ , 1-21% of Yb 3+ and the balance of Tm 3+; the end-capping agent is a branched polymer; the solvent is ethylene glycol; the molar ratio of the rare earth salt, ammonium fluoride, sodium chloride and end-capping agent is (0.1-0.8):(0.3-5):(0.1-2):(0.001-0.01) (further preferably, (0.1-0.3):(0.3-1):(0.1-0.5):(0.001-0.01)); the temperature of the reaction 2 is 150-200 ℃, and the time is 1-3 h. The amount of ethylene glycol is not specially limited in the present application, and the amount thereof can satisfy the reaction 2.

[0022] Further preferably, the branched polymer is branched polyethyleneimine (BPEI).

[0023] In the preferred embodiment of the present application, the zirconium salt is zirconium tetrachloride; the organic ligand is 2-amino terephthalic acid; the adjusting agent is glacial acetic acid; the mass ratio of the zirconium tetrachloride, 2-amino terephthalic acid and glacial acetic acid is (50-150):(70-200):(6-30); after the NaYF4:Yb,Tm upconversion nanoparticles are dispersed in the solution 1, the content of the NaYF4:Yb,Tm upconversion nanoparticles in the obtained mixed solution is 5-60 mg; The temperature of the reaction 1 is 100-150 ℃, and the time is 1.5-3.5 h.

[0024] In the preferred embodiment of the present application, the solvent in the solution 1 is N,N-dimethylformamide (DMF). The amount of DMF is not specially limited in the present application, and the amount thereof can satisfy the reaction 1.

[0025] In the preferred embodiment of the present application, the coupling agent is 4-(4,6-dimethoxytriazin-2-yl)-4-methylmorpholinium chloride (DMTMM); the mass ratio of the coupling agent and chain transfer agent CPCP (4-cyano-4-(phenylcarbonylthio)pentanoic acid) is (2-6):1; the mass ratio of the chain transfer agent CPCP and upconversion functionalized MOF nanocomposite is (2.5-6.5):1; the temperature of the amidation reaction is room temperature, and the time is 6-24 h.

[0026] In the preferred embodiment of the present application, the polymerization monomer is a methacrylic compound; the initiator is an azo initiator; the ratio of the upconversion functionalized MOF nanocomposite, polymerization monomer and initiator is 50-70 mg:24-27 mmol:0.04-0.06 mmol; The temperature of the polymerization reaction is 50-70 ℃, and the time is 6-24 h.

[0027] Further preferably, the methacrylic compound is methacrylic acid (MAA); and the azo initiator is ACVA (4,4'-azobis(4-cyanopentanoic acid)).

[0028] In the preferred embodiment of the present application, the content of the multifunctional MOF nanocomposite in the mixed solution is 0.2-2.4 g / L (further preferably, 0.2-1 g / L), the content of ammonia is 5-30 g / L (further preferably, 20-30 g / L), and the concentration of silver ions is 5-20 g / L (further preferably, 8-15 g / L); and the mass ratio of the multifunctional MOF nanocomposite to sodium dihydrogen phosphate is 1:(20-23).

[0029] In the preferred embodiment of the present application, the temperature of the standing reaction is 20-30 ℃, and the time is 8-48 h (further preferably, 24-48 h).

[0030] The second aspect of the present application provides a high-efficiency near-infrared responsive photocatalytic composite crystal (ternary composite silver phosphate crystal) prepared by the above preparation method.

[0031] The ternary composite silver phosphate crystal provided by the present application has a particle size of about 100-400 μm.

[0032] The ternary composite silver phosphate crystal provided by the present application first uses a multifunctional MOF (UiO-66-NH2) nanocomposite as a guest particle, and then biomimetic synthesis is performed to embed it in a silver phosphate single crystal to obtain a multifunctional ternary composite silver phosphate material. During the growth of the silver phosphate crystal, the multifunctional MOF (UiO-66-NH2) is anchored to the crystal face and gradually fused with the crystal to form a ternary composite silver phosphate crystal.

[0033] The third aspect of the present application provides an application of the above high-efficiency near-infrared responsive photocatalytic composite crystal in photocatalytic degradation of rhodamine B.

[0034] In the preferred embodiment of the present application, in the photocatalytic degradation of rhodamine B, the concentration of rhodamine B in the rhodamine B-containing wastewater is 10 mg / L, and the amount of the high-efficiency near-infrared responsive photocatalytic composite crystal used is 0.5-1 mg / mL; the wavelength of the light used in the photocatalysis is 980 nm, and the intensity is 0.475 W.

[0035] The technical solutions of the present application, if not specifically stated, are conventional solutions in the art, and the reagents or raw materials used, if not specifically stated, are purchased from commercial channels or are already disclosed.

[0036] In order to better understand the present application, the following further illustrates the content of the present application in conjunction with examples, but the content of the present application is not limited to the following examples only.

[0037] Example 1 The preparation process of NaYF4:Yb, Tm upconversion nanoparticles is as follows: Sodium chloride (NaCl, 84 mg, 1.438 mmol), yttrium chloride hexahydrate (YCl3·6H2O, 153 mg, 0.501 mmol), ytterbium chloride hexahydrate (YbCl3·6H2O, 50 mg, 0.130 mmol), thulium chloride hexahydrate (TmCl3·6H2O, 5 mg, 0.013 mmol) and branched polyethyleneimine (BPEI, 0.3 g, 0.006 mmol) were dissolved in 6 mL ethylene glycol (EG). Then, a solution containing ammonium fluoride (NH4F, 150 mg, 4.05 mmol) in 6 mL EG was added to the solution. After stirring for 10 minutes, the mixture was transferred to a 50 mL polyacrylonitrile-lined autoclave and reacted at 200 ℃ for 3 hours. The obtained nanoparticles were collected by centrifugation at 10000 rpm, washed with ethanol and deionized water, and finally redispersed in 10 mL N,N-dimethylformamide (DMF) to obtain a NaYF4:Yb, Tm dispersion with a concentration of about 10 mg / mL. Figure 1 The transmission electron microscope picture of NaYF4:Yb, Tm is shown, and the inset is a digital photograph of upconversion luminescence under 980 nm near-infrared light excitation.

[0038] Example 2 The preparation process of upconversion functionalized UiO-66-NH2 nanocomposites (NaYF4:Yb, Tm / UiO-66-NH2 nanocomposites) is as follows: Zirconium tetrachloride (ZrCl4, 122 mg, 0.526 mmol) and 2-aminoterephthalic acid (BDC-NH2, 174 mg, 0.959 mmol) were dissolved in 120 mL DMF in a 250 mL round-bottom flask, and then acetic acid (10 mL) was added. After the obtained solution was ultrasonically treated for 15 minutes, a 5 mL DMF solution containing NaYF4:Yb, Tm nanoparticles (60 mg) was added. The mixture was continuously ultrasonically treated for 5 minutes and sealed, and then transferred to an oil bath preheated to 150 ℃ and reacted for 3 hours. The nanocomposites were collected by centrifugation at 9500 rpm, washed with DMF three times, washed with methanol twice, and finally dispersed in 10 mL methanol for standby use (5 mg / mL). Figure 2 The transmission microscope picture of upconversion functionalized UiO-66-NH2 nanocomposites is shown.

[0039] As a control, the preparation of upconversion functionalized UiO-66-NH2nanoparticles was the same as that of the upconversion functionalized UiO-66-NH2nanocomposite, except that the addition of NaYF4: Yb, Tm nanoparticles was omitted.

[0040] Example 3 The preparation process of the multifunctionalized UiO-66-NH2nanocomposite (NaYF4: Yb, Tm / UiO-66-PMAA nanocomposite) was as follows: The NaYF4: Yb, Tm / UiO-66-NH2nanocomposite (60 mg) was dispersed in 30 mL of methanol in a round-bottom flask. CPCP (186 mg, 0.668 mmol) and DMTMM (746 mg, 2.698 mmol) were added under continuous stirring. After 12 h of reaction, the upconversion functionalized UiO-66-NH2nanocomposite grafted with CPCP was collected by centrifugation and washed four times with methanol. The grafted nanocomposite was redispersed in 10 mL of methanol, and methacrylic acid (MAA, 2.29 g, 26.648 mmol) and ACVA (16 mg, 0.053 mmol) were added successively. The reaction system was sealed and placed in an ice-water bath for 20 min with nitrogen bubbling, and then transferred to a preheated oil bath at 70 °C for 24 h of stirring to initiate polymerization. After the reaction, the multifunctionalized UiO-66-NH2nanocomposite was collected by centrifugation, washed three times with methanol and four times with deionized water, and finally redispersed in 10 mL of deionized water for use. Figure 3 The transmission microscope image of the multifunctionalized UiO-66-NH2nanoparticles.

[0041] As a control, the preparation of UiO-66-PMAA nanoparticles was the same as that of the multifunctionalized UiO-66-NH2nanocomposite, except that the NaYF4: Yb, Tm / UiO-66-NH2nanocomposite was replaced by the upconversion functionalized UiO-66-NH2nanoparticles in Example 2.

[0042] Example 4 The preparation process of the ternary composite silver phosphate crystal (NaYF4: Yb, Tm / UiO-66-PMAA@Ag3PO4 composite crystal) was as follows: First, silver nitrate (AgN03, 240 mg, 1.41 mmol) was dissolved in 0.30 mL of deionized water, and then 10 mL of an aqueous ammonia solution (containing 408 mg of ammonia) was added. After stirring for 10 minutes, 5 mL of a deionized water solution containing NaYF4: Yb, Tm / UiO-66-PMAA nanocomposites (8 mg) was added to the solution, and stirring was continued for 15 minutes. Then, 3 mL of a deionized water solution containing sodium hydrogen phosphate (Na2HP04, 170 mg, 2.395 mmol) was added, and stirring was continued for 3 minutes. After standing for 24 hours, the precipitate was the obtained NaYF4: Yb, Tm / UiO-66-PMAA@Ag3P04 composite crystal. Figure 4 Figure 6 is a scanning electron microscope image of the ternary composite silver phosphate crystal.

[0043] As a control, the preparation of blank Ag3P04 crystals was the same as that of the NaYF4: Yb, Tm / UiO-66-PMAA@Ag3P04 composite crystal, except that no NaYF4: Yb, Tm / UiO-66-PMAA nanocomposites were added.

[0044] Material characterization: The different materials were characterized by Fourier-exchange infrared spectrometer (FTIR). Figure 5 By comparing the infrared characteristic peaks of different materials, it can be proved that the multifunctional UiO-66-NH2 nanocomposites and the NaYF4: Yb, Tm / UiO-66-PMAA@Ag3P04 composite crystal were successfully prepared.

[0045] Performance test: The photocatalytic degradation of Rhodamine B (RhB) under near-infrared light irradiation was carried out under 980 nm near-infrared light (0.475 W) irradiation. The typical process was as follows: 10 mg of photocatalyst was dispersed in 15 mL of RhB aqueous solution (10 mg / L), and after 90 minutes of magnetic stirring in the dark to establish adsorption-desorption equilibrium, light irradiation was started. During the photocatalytic reaction, 1 mL of sample was collected at a predetermined time interval (10 min, 20 min, 30 min, 40 min), and after centrifugation (10,000 rpm, 5 minutes) to separate the photocatalyst, the RhB residual concentration in the supernatant was analyzed. The RhB degradation rate was calculated by the following formula: Figure 6 As can be seen, NaYF4: Yb, Tm / UiO-66-PMAA and Ag3P04 cannot complete the near-infrared light response catalysis alone (the degradation curves corresponding to the two materials within forty minutes almost have no change), while NaYF4: Yb, Tm / UiO-66-PMAA@Ag3P04 can effectively degrade Rhodamine B under near-infrared light excitation (40 minutes to complete degradation).

[0046] Cycling study The photocatalyst (NaYF4:Yb,Tm / UiO-66-PMAA@Ag3PO4 composite crystals of Example 4) recovered by centrifugation was washed twice with deionized water and dried before use in the subsequent cycling experiments. The photocatalyst was recovered by centrifugation after each cycle and reused in the next cycle. Figure 7 It can be seen that the photocatalyst still maintains high catalytic performance after 10 cycles.

[0047] The above only describes the preferred embodiments of the present application, and it should be noted that for those skilled in the art, without departing from the principles of the present application, a number of improvements and refinements can be made, and these improvements and refinements should also be considered as the protection scope of the present application.

Claims

1. A method for preparing a highly efficient near-infrared responsive photocatalytic composite crystal, characterized in that, Includes the following steps: NaYF4:Yb,Tm upconversion nanoparticles were dispersed in solution 1 and reacted in step 1 to obtain upconversion functionalized MOF nanocomposite material. The solute in solution 1 is a zirconium salt, an organic ligand, and a regulator; The upconversion functionalized MOF nanocomposite material undergoes an amidation reaction with chain transfer agent CPCP under the action of a coupling agent to obtain CPCP-grafted upconversion functionalized MOF nanocomposite material. The upconversion functionalized MOF nanocomposite material grafted with CPCP undergoes a polymerization reaction with polymer monomers under the action of an initiator to obtain a multifunctional MOF nanocomposite material. The multifunctional MOF nanocomposite material was dispersed in silver ammonia solution to obtain a mixed solution; then sodium dihydrogen phosphate was added to the mixed solution and allowed to stand for reaction to obtain the photocatalytic composite crystal.

2. The preparation method according to claim 1, characterized in that, The preparation method of the NaYF4:Yb,Tm upconversion nanoparticles is as follows: rare earth salt, ammonium fluoride, sodium chloride and end-capping agent are added to a solvent and reacted 2.

3. The preparation method according to claim 2, characterized in that, The rare earth salt comprises 77%-98% Y by molar percentage. 3+ 1-21% of Yb 3+ and margin Tm 3+ The capping agent is a branched polymer; the solvent is ethylene glycol; the molar ratio of the rare earth salt, ammonium fluoride, sodium chloride and capping agent is (0.1-0.8):(0.3-5):(0.1-2):(0.001-0.01); the temperature of reaction 2 is 150-200 ℃ and the time is 1-3 h.

4. The preparation method according to claim 1, characterized in that, The zirconium salt is zirconium tetrachloride; the organic ligand is 2-aminoterephthalic acid; the regulator is glacial acetic acid; the mass ratio of zirconium tetrachloride, 2-aminoterephthalic acid and glacial acetic acid is (50-150):(70-200):(6-30); after dispersing NaYF4:Yb,Tm upconversion nanoparticles in solution 1, the content of NaYF4:Yb,Tm upconversion nanoparticles in the resulting mixed solution is 5-60 mg; The temperature of reaction 1 is 100-150 °C, and the time is 1.5-3.5 h.

5. The preparation method according to claim 1, characterized in that, The coupling agent is 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride; the mass ratio of the coupling agent to the chain transfer agent CPCP is (2-6):1; the mass ratio of the chain transfer agent CPCP to the upconversion functionalized MOF nanocomposite material is (2.5-6.5):1; the amidation reaction is carried out at room temperature for 6-24 h.

6. The preparation method according to claim 1, characterized in that, The monomer is a methacrylic acid compound; the initiator is an azo initiator; the ratio of the upconversion functionalized MOF nanocomposite material, the monomer, and the initiator is 50-70 mg: 24-27 mmol: 0.04-0.06 mmol. The polymerization reaction is carried out at a temperature of 50-70 °C for 6-24 h.

7. The preparation method according to claim 1, characterized in that, The mixed solution contains 0.2-2.4 g / L of multifunctional MOF nanocomposite material, 5-30 g / L of ammonia, and 5-20 g / L of silver ions; the mass ratio of the multifunctional MOF nanocomposite material to sodium dihydrogen phosphate is 1:(20-23).

8. The preparation method according to claim 1, characterized in that, The static reaction is carried out at a temperature of 20-30 °C for 8-48 h.

9. A highly efficient near-infrared responsive photocatalytic composite crystal prepared by the preparation method according to any one of claims 1-8.

10. The application of the high-efficiency near-infrared responsive photocatalytic composite crystal of claim 9 in the photocatalytic degradation of Rhodamine B.

Citation Information

Patent Citations

  • Inorganic nonmetallic mineral composite material loaded with titanium dioxide layer, preparation method and application thereof

    CN102962045A

  • Silver phosphate / titanium dioxide nanocomposite and preparation method thereof

    CN104383947A

  • Preparation method of ternary composite photocatalyst BiOI@UNCN (UIO-66(NH2)@g-C3N4)

    CN109395777A

  • Material for improving photocatalytic oxygen production activity and stability of Ag3PO4 and preparation method thereof

    CN114797990A

  • Photocatalytic device with silver phosphate loaded in transparent medium tube and preparation method

    CN115475635A